Spectroscopic elucidation of ionic motion processes in tunnel oxide-based memristive devices. (26th October 2018) - Baeumer, Christoph; Heisig, Thomas; Arndt, Benedikt; Skaja, Katharina; Borgatti, Francesco; Offi, Francesco; Motti, Federico; Panaccione, Giancarlo; Waser, Rainer; Menzel, Stephan; Dittmann, Regina
Abstract : Operando photoelectron spectroscopy of memristive devices indicates a reversible shift of oxygen during biasing which proceeds even after device breakdown. Abstract : Resistive switching oxides are highly attractive candidates to emulate synaptic behaviour in artificial neural networks. Whilst the most widely employed systems exhibit filamentary resistive switching, interface-type switching systems based on a tunable tunnel barrier are of increasing interest, since their gradual SET and RESET processes provide an analogue-type of switching required to take over synaptic functionality. Interface-type switching devices often consist of bilayers of one highly mixed-conductive oxide layer and one highly insulating tunnel oxide layer. However, most tunnel oxides used for interface-type switching are also prone to form conducting filaments above a certain voltage bias threshold. We investigated two different tunnel oxide devices, namely, Pr1− x Ca x MnO3 (PCMO) with yttria-stabilized ZrO2 (YSZ) tunnel barrier and substoichiometric TaO x with HfO2 tunnel barrier by interface-sensitive, hard X-ray photoelectron spectroscopy (HAXPES) in order to gain insights into the chemical changes during filamentary and interface-type switching. The measurements suggest an exchange of oxygen ions between the mixed conducting oxide layer and the tunnel barrier, that causes an electrostatic modulation of the effective height of the tunnel barrier, as the underlying switching mechanism for the interface-type switching. Moreover, we observe by in operando HAXPES analysis that this field-driven ionic motion across the whole area is sustained even if a filament is formed in the tunnel barrier and the device is transformed into a filamentary-type switching mode.